Indigenous Australians and the National Disability Insurance Scheme - Biddle, N. (ANU Press, 2014)
The National Disability Insurance Scheme (NDIS) is one of the major policy innovations of the early 21st century in Australia, representing a new way of delivering services to people with a disability and those who care for them.